(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
It is evident that a number of distinct factors are involved in the performance of an employee: his inborn abilities and his character traits; the basic knowledge and the experience he has acquired in the past; and above all, the degree to which he is motivated. In this article consideration is given to motivation as being the factor which has the strongest and the most rapid influence. Our primary objective was to investigate the effectiveness of different methods for enhancing employee motivation in an organization. An initial point to underline in connection with the findings of this study is that we have devised a definition for an additional category that we have examined, one which involves factors that improve performance not because they involve some specific benefits that may be obtained, but because they make it possible to avoid some unpleasant circumstances that could develop if performance is not improved. We refer to these factors as «adverse consequence avoidance factors»: they could be linked with the fear of receiving sharp criticism from a superior, the fear of being observed by others during the process of being reprimanded, or ultimately the fear of being discharged. A survey was conducted to devise a ranking of the various factors in terms of their influence on personnel productivity. The results of the study demonstrate that the employees’ fear of being discharged or of receiving a sharp criticism from their superior are important factors, that increase productivity of Ukrainian workers. Moreover, the results of the survey indicated that there are three factors which influence labour productivity more than any others – having a satisfactory basic salary, obtaining bonuses and receiving verbal or written recognition. Having access to free parking or feeling that one’s job provides a personal challenge are considered to be less influential factors. However, there are significant differences between the groups with respect to some specific factors. The combinations of monetary and non-monetary incentives that have the highest influence on employee performance are suggested for different staff groups: top, middle and low level managers, and professional and supporting staff.